2016
DOI: 10.1186/s13075-016-0979-0
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell-derived mesenchymal stromal cells ameliorate collagen-induced arthritis by inducing host-derived indoleamine 2,3 dioxygenase

Abstract: BackgroundThe immunosuppressive and anti-inflammatory properties of mesenchymal stromal cells (MSC) have prompted their therapeutic application in several autoimmune diseases, including rheumatoid arthritis. Adult MSC are finite and their clinical use is restricted by the need for long-term expansion protocols that can lead to genomic instability. Inhibition of Smad2/3 signaling in human pluripotent stem cells (hPSC) provides an infinite source of MSC that match the phenotype and functional properties of adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 49 publications
0
29
0
1
Order By: Relevance
“…Consistent with these findings, recent investigations have revealed that MSCs regulate the inflammatory processes through various soluble factors such as indoleamine 2,3-dioxygenase, TGF-β, prostaglandin E2 (PGE2), and TSG-6 31, 4648 . Among these, TSG-6 has been shown to be pivotal for the anti-inflammatory effects of MSCs in corneal inflammation, severe burn injury, acute lung injury, acute peritonitis, pancreatitis, and IBD 13, 16, 17, 47, 49, 50 .…”
Section: Discussionmentioning
confidence: 55%
“…Consistent with these findings, recent investigations have revealed that MSCs regulate the inflammatory processes through various soluble factors such as indoleamine 2,3-dioxygenase, TGF-β, prostaglandin E2 (PGE2), and TSG-6 31, 4648 . Among these, TSG-6 has been shown to be pivotal for the anti-inflammatory effects of MSCs in corneal inflammation, severe burn injury, acute lung injury, acute peritonitis, pancreatitis, and IBD 13, 16, 17, 47, 49, 50 .…”
Section: Discussionmentioning
confidence: 55%
“…In addition, it was demonstrated that human ES-MSCs can inhibit CD83 up-regulation and IL-12p70 secretion from dendritic cells and increase T-reg cell populations after induction by IL-2 . The therapeutic potentials of ES-and iPS-MSCs have been investigated in many animal models such as inflammatory bowel disease (Sanchez et al, 2011), fistulizing Crohn's disease (Ferrer et al, 2016), experimental autoimmune encephalitis (Wang et al, 2014), cardiac remodeling and dysfunction (Liang et al, 2017), arthritis (Gonzalo-Gil et al, 2016), lupus nephritis (Thiel et al, 2015), cardiomyopathy , diabetes (Hajizadeh-Saffar et al, 2015) and pulmonary arterial hypertension . We also reported the therapeutic effect of human ES-MSC on acute hepatic failure (Lotfinia et al, 2016) and lethal fulminant hepatic failure models (Moslem, Valojerdi, Pournasr, Muhammadnejad & Baharvand, 2013 (Feng, Mantesso, De Bari, Nishiyama & Sharpe, 2011) and autophagy (Jung et al, 2013) through their secretome Huang et al, 2016;Konala et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Transplanted ps‐MSCs remarkably attenuate severe hind‐limb ischemia in mice via direct differentiation and paracrine mechanisms and provide a stronger therapeutic effect than BM‐MSCs on vascular and muscle regeneration . Moreover, ps‐MSCs reduce the symptoms in mice with a variety of inflammatory and autoimmune disease such as allergy airway inflammation , lupus, uveitis, collagen‐induced arthritis , and inflammatory bowel disease (IBD) . ps‐MSCs improve clinical abnormalities in IBD by promoting intestinal epithelial cell proliferation, increasing Lgr5 + intestinal stem cells, and stimulating intestinal angiogenesis .…”
Section: Therapeutic Effects Of Ps‐mscs In Vivomentioning
confidence: 99%